115k views
4 votes
Identify the equivalent expression for each of the expressions below. Root(5, (m + 2) ^ 3). Root(3, (m + 2) ^ 5). Root(5, m ^ 3) + 2. Root(3, m ^ 5) + 2

User Loveky
by
5.5k points

1 Answer

6 votes

Answer:

1.
(\sqrt[5]{(m+2)})^(3) = (m+2)^{(3)/(5)}

2.
(\sqrt[3]{(m+2)})^(5) = (m+2)^{(5)/(3)}

3.
\sqrt[5]{(m)}^(3)+2 = m^{(3)/(5)}+2

4.
\sqrt[3]{(m)}^(5)+2 = m^{(5)/(3)}+2

Explanation:

Recall that


(\sqrt[n]{x})^(m) = (x^{(m)/(n)})

Where
x^(m) is called radicand and n is called index

1. Root(5, (m + 2) ^ 3)

In this case,

n is 5

m is 3

x = (m + 2)


(\sqrt[5]{(m+2)})^(3) = (m+2)^{(3)/(5)}

2. Root(3, (m + 2) ^ 5)

In this case,

n is 3

m is 5

x = (m + 2)


(\sqrt[3]{(m+2)})^(5) = (m+2)^{(5)/(3)}

3. Root(5, m ^ 3) + 2

In this case,

n is 5

m is 3

x = m


\sqrt[5]{(m)}^(3)+2 = m^{(3)/(5)}+2

4. Root(3, m ^ 5) + 2

In this case,

n is 3

m is 5

x = m


\sqrt[3]{(m)}^(5)+2 = m^{(5)/(3)}+2

User Noa
by
5.4k points